Creative Selection between Emending and Forming Medieval Memory - Scholz, Sebastian; Schwedler, Gerald (Millennium-Studien / Millennium Studies, 2021)
How can it be, that only as much happens as fits into the newspaper the next day? (K. Valentin). Information of the past has to be organised, arranged and selected. The process of selection must be seen as the fundamental moment of making History. This book shows selection as creative act. With the richness of early medieval material it can be demonstrated that creative selection was omnipresent and took place even in unexpected text genres.